Christian-Muslim Relations in Indonesia: Five Challenges of the Twenty-First Century - Rabi, Ibrahim Abu (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1998)
This paper - inspired by the